Perampanel-Induced Psychosis in a Young Woman: A Case Report. Issue 6 (November 2021) - Pujal Rodríguez, Ester; Pons-Cabrera, María Teresa; Giménez, Anna; Colomer, Lluc; Baldaqui, Núria; Gutiérrez, Felipe; Anmella, Gerard; Ilzarbe, Lidia; Madero, Santiago; Sagué-Vilavella, Maria; Olivera, Marta; Santana, Daniel; et al.
Abstract : Objectives: A case of perampanel-induced psychosis in a young woman is reported, a side effect that has only rarely been reported in the literature. Methods: We describe a case of a young woman with epilepsy and no psychiatric history with perampanel-associated altered behavior and psychotic symptoms, requiring hospitalization in an acute psychiatry ward. We also provide a literature review on the possible neurobiological pathways implicated. Results: Perampanel is believed to block a small proportion of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor current, retarding epileptiform discharges while sparing most normal synaptic transmission. Most common adverse events are related to central nervous system (including dizziness, drowsiness, blurred vision and imbalance) and psychiatric symptoms have been reported. Conclusions: The biological vulnerability to psychiatric and behavioral adverse reactions of antiepileptic drugs is multifactorial and different mechanisms and clinical predisposing factors may interact. For this reason, patients starting these antiseizure drugs need long-term and comprehensive clinical monitoring.